Proposal for the Creation of a Cluster to Boost Sustainable Economic Development in Sao Tomé through Organic Cocoa Cultivation - Pimenta-Alonso, Andrea Mara; Prazeres, Ibrahim; Lucas, Maria Raquel (Transformations In Business & Economics, 2024)
This article aims to evaluate the advantages and disadvantages of creating a cluster of small and medium entrepreneurs within STP’s organic cocoa production. To this end, the study carried out mixed research, both qualitative and with multiple case studies. The qualitative approach focused on the production of organic cocoa in STP, seeking explanations for the clustering phenomenon and responses to the research questions so as to understand them in temporal, local and cultural contexts. The quantitative data originated from case studies of clusters in Portugal, Spain and Brazil. The results revealed that the improvement of economic efficiency and the size of cluster-participating companies are the most important advantages. It is clear that an organised sector increases the welfare of the regions where it is established. The most important disadvantages are the need to invest in administrative structure and technical support and the need to dismantle negative biases on innovation initiatives.